Grenzen und Strafe in der Heimerziehung Eine sozialpädagogische Studie - Huber, Sven (Verlag Barbara Budrich, 2019)
The book deals with current debates in Social Pedagogy on issues of setting limits, doing border and punishment in residential care. Their main arguments and (de-)legitimating figures as well as their narrowness of perspective and blind spots are discussed. As part of an empirical case study, key dimensions of doing border are then worked out and placed in a systematic relationship with the current debates.